Passazhir poeėda no 12 - e; e; Intercinema ([Moscow] : Gorky Film Studio, 1998)
--
Editor, A. Strulyov.
In Russian; with English subtitles.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed August 30, 2017).
Keywords: Tolstoy, Leo, -- graf, -- 1828-1910 -- Last years; Tolstoy, Leo, -- graf, -- 1828-1910 -- Death and burial; Russia -- History -- 1904-1914.; Biographical films; Documentary films; Nonfiction films; Internet videos; Streaming video